Creative Economy Development Strategy In Banyumas Regency - Sidik Rohiwan (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2022)
The creative economy is a sector that has great opportunities to develop and make an economic contribution to the people of Banyumas Regency. This study aims to identify the strengths, weaknesses, opportunities and threats as a basis for planning the development of a creative economy in Banyumas Regency. The research was conducted using a qualitative method with a literature study approach. The results of the research show that the role of the creative economy community is very important in terms of public policy and has considerable strengths as well as opportunities.